Combining Stem Cell Therapy for Advanced Heart Failure and Ventricular Assist Devices: A Review. Issue 5 (September 2018) - Reich, Heidi J.; Czer, Lawrence S. C.; Ramzy, Danny; Arabia, Francisco; Moriguchi, Jaime; Ascheim, Deborah D.; Henry, Timothy D.
Abstract : The use of stem cell therapy in combination with a left ventricular assist device (LVAD) for patients with advanced heart failure (HF) is an attractive concept with the potential to alter the natural history of HF. Cell therapy trials for HF have demonstrated excellent safety and encouraging results, but current rates of myocardial recovery after LVAD implantation are limited. Early trials combining these 2 therapies to increase the likelihood of recovery and to potentially obviate the need for subsequent transplantation appear promising. Additionally, the application of cell therapy to patients undergoing LVAD implantation as a bridge to cardiac transplantation creates an opportunity to examine cardiac tissue before and after treatment and to study the mechanism of benefit. Despite the promise, there is a paucity of data for the combination of stem cell therapy with LVAD insertion in patients with HF. Of 11 case series or clinical trials, the largest enrolled 30 patients. We highlight clinical trials using stem cell therapy for end-stage HF most relevant to an LVAD patient population and comprehensively review the preclinical and clinical studies of combined stem cell therapy and long-term mechanical circulatory support. Based on the available clinical trials, the combination of stem cell therapy and LVAD support is a promising approach but requires further clinical refinement, with additional clinical data and larger numbers of patients required to support its clinical application.